Essential commodities prices, availability, and market actors’ perceptions: March 2025 - Siddig, Khalid; Nigus, Halefom Yigzaw; Rakhy, Tarig; Mohamed, Shima; Abushama, Hala (International Food Policy Research Institute., 2025)
Sudan’s market systems continue to face severe disruptions due to ongoing conflict, political instability, and economic disruptions. These challenges have led to volatile prices, limited availability of essential commodities, and rising food and fuel costs, especially in conflict-affected areas. Insecurity, infrastructure damage, and transport disruptions further exacerbate price disparities, making key goods increasingly unaffordable for vulnerable populations. To monitor these dynamics, the International Food Policy Research Institute (IFPRI) is implementing a nationwide market monitoring initiative covering 36 markets, two in each of Sudan’s 18 states. The initiative tracks prices, availability, and quality of essential commodities, monitors exchange rate movements, and gathers qualitative insights from market actors. Each month, data is collected in two rounds: the first during the first two weeks, and the second during the last two weeks. In each round, five merchants per market are interviewed using structured questionnaires and semi-structured interviews. This fortnightly approach enables timely and consistent tracking of market trends.